Cortical Thickness Related to Compensatory Viewing Strategies in Patients With Macular Degeneration - Plank, Tina; Benkowitsch, Edith M. A.; Beer, Anton L.; Brandl, Sabine; Malania, Maka; Frank, Sebastian M.; Jägle, Herbert; Greenlee, Mark W. (Frontiers in Neuroscience, 2021)
Retinal diseases like age-related macular degeneration (AMD) or hereditary juvenile macular dystrophies (JMD) lead to a loss of central vision. Many patients compensate for this loss with a pseudo-fovea in the intact peripheral retina, the so-called “preferred retinal locus” (PRL). How extensive eccentric viewing associated with central vision loss (CVL) affects brain structures responsible for visual perception and visually guided eye movements remains unknown. CVL results in a reduction of cortical gray matter in the “lesion projection zone” (LPZ) in early visual cortex, but the thickness of primary visual cortex appears to be largely preserved for eccentric-field representations. Here we explore how eccentric viewing strategies are related to cortical thickness (CT) measures in early visual cortex and in brain areas involved in the control of eye movements (frontal eye fields, FEF, supplementary eye fields, SEF, and premotor eye fields, PEF). We determined the projection zones (regions of interest, ROIs) of the PRL and of an equally peripheral area in the opposite hemifield (OppPRL) in early visual cortex (V1 and V2) in 32 patients with MD and 32 age-matched controls (19 to 84 years) by functional MRI. Subsequently, we calculated the CT in these ROIs and compared it between PRL and OppPRL as well as between groups. Additionally, we examined the cortical thickness of FEF, SEF and PEF and correlated it with behavioral measures like reading speed and eccentric fixation stability at the PRL. We found a significant difference between PRL and OppPRL projection zones in V1 with increased CT at the PRL, that was more pronounced in the patients, but also visible in the controls. Although the mean CT of the eye fields did not differ significantly between patients and controls, we found a trend to a positive correlation between CT in the right FEF and SEF and fixation stability in the whole patient group and between CT in the right PEF and reading speed in the JMD subgroup. The results indicate a possible association between the compensatory strategies used by patients with CVL and structural brain properties in early visual cortex and cortical eye fields.